Electronique de puissance - REZINI, S. (My University, 2024)
presents the semiconductor devices used as well as their characteristics, and analyzes the operation of the main converters by studying their waveforms, calculating efficiency, and applications. The workbook is divided into two complementary parts. The first part provides concise theoretical reviews on trigonometric functions, solving differential equations, laws of electricity, power/efficiency calculations, as well as a summary on static converters. The second part offers corrected exercise sheets covering periodic quantities/Fourier series, powers/efficiency, power semiconductors, single-phase, bi-phase and three-phase controlled/uncontrolled rectifiers, choppers, inverters and AC regulators. Keywords: Power electronic devices, static converter, diode, thyristor, transistor, rectifier, AC regulator, chopper, inverter.
Polycopié de Travaux Dirigés
Keywords: Electronique de puissance; convertisseur statique; diode; thyristor; transistor; redresseur; gradateur; hacheur; onduleur